2017
DOI: 10.4314/bajopas.v9i2.6
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS analysis of ethyl acetate extract of <i>Ficus sycomorus</i> root Linn. (Moraceae

Abstract: Gas Chromatography-Mass Spectrometry (GC chromatography of the ethyl acetate extract of Ficus sycomorus Linn. root two compounds. The mass spectral data shows that all the compounds have molecular ion peak and base peak with M/Z 468 and 218 respectively. The tentative identification was achieved by comparing their mass spectra with the data sys compounds are suggested to be pentacyclic triterpenoid isomers, and this include; 12 yl, acetate (3.alpha) and Urs-12-en sycomorus suggests that the plant conforms to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Steroids is absent in both extracts. This agreed with previous findings [36][37][38][39]. In another study using root back extract of the same plant, reducing sugar was also found [40].…”
Section: Phytochemical Constituents Of F Sycomorus Stem Bark Extractssupporting
confidence: 92%
“…Steroids is absent in both extracts. This agreed with previous findings [36][37][38][39]. In another study using root back extract of the same plant, reducing sugar was also found [40].…”
Section: Phytochemical Constituents Of F Sycomorus Stem Bark Extractssupporting
confidence: 92%
“…This analysis was performed to study the effects of gamma rays on secondary compounds of (Ficus palmata) the best doses of gamma 30 &40 Gray, as they increased the secondary compounds of the plant. These results were confirmed by (Abubakar et al, 2016) 15-methyltricyclo[6.5.2(13,14).0(7,15)]pentadeca-1,3,5,7,9,11,13-heptene 25.79 C16H14 206 23.30 Acetic acid,10,7,7, [6.5.2(13,14).0(7,15)]pentadeca-1, 3,5,7,9,11,13- (5,6,7,8-tetrahydro-2,8,8-trimethyl-4h-cyclohepta[b]furan-5-yl)-…”
Section: Effect Of Radiation On Secondary Compounds In Callus Of Ficu...supporting
confidence: 65%
“…The mass spectrometric detector was operated in an electron impact ionization mode with an ionizing energy of 70 eV. (Abubakar et al, 2016).…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Abubakar et al, [40] reported that, the leaves of Fiscus sycomorus have antidiabetic, antioxidant, antitumor, and antibacterial activity. Also the aqueous extract of stem bark exhibits sedative, anticonvulsant and muscular activities due to the present of alkaloids, flavonoids and other phytoconstituents.…”
Section: Pharmacological Activities Of Nigerian Medicinal Plantsmentioning
confidence: 99%